Novel SnO₂ based optical sensor for detectin of low ammonia concentration in water at room temperatures - Pisco, M.; Consales, M.; Viter, R.; Smyntyna, V.; Campopiano, S.; Giordano, M.; Cusano, A.; Cutolo, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
In the work, presented are preliminary experimental results on the capability of a metal oxide (MO) based optical sensor to perform ammonia detection in water environment at room temperature. The electro-spray pyrolysis technique was used to deposit SnO₂ films on the distant end of standard silica optical fiber (SOF). Reflection spectra of the studied samples were preliminarily characterized in the range of 1520 to 1620 nm by using a tunable laser and an optical spectrum analyzer. Single wavelength reflectance measurements were carried out to test the sensing performances for detecting the ammonia of concentration from 4 to 20 ppm. High sensitivity to the target analyte and fast response times were observed. From the results obtained, the detection limit close to a sub-ppm level was achieved.